Ask Question
18 September, 12:41

Use function notation to write a recursive formula to represent the sequence: 3, 6, 12, ...

f (n) = f (n - 1) + 3

f (n) = f (n - 1) + 2

f (n) = f (n-1).3

f (n) = f (n-1) 2

+4
Answers (1)
  1. 18 September, 13:15
    0
    f (n) = f (n-1) * 2

    Step-by-step explanation:

    The previous term is being multiplied by 2 to get a term.

    First term is 3.

    Second term is 3*2=6.

    Third term is 6*2=12.

    ...

    nth term is f (n-1) * 2.

    Note: f (n-1) is just the term before f (n).

    f (n) = f (n-1) * 2 with f (1) = 3 is the recursive form for this sequence.
Know the Answer?
Not Sure About the Answer?
Find an answer to your question ✅ “Use function notation to write a recursive formula to represent the sequence: 3, 6, 12, ... f (n) = f (n - 1) + 3 f (n) = f (n - 1) + 2 f ...” in 📘 Mathematics if you're in doubt about the correctness of the answers or there's no answer, then try to use the smart search and find answers to the similar questions.
Search for Other Answers